Analisis Layanan Kurban Berbasis Teknologi Digital Menggunakan Analytical Network Process dan New Product Development pada Platform Sebisaku (Semua Bisa Kurban) - Salat, Roy; Pratiwi, Emmy (Ranah Research : Journal of Multidisciplinary Research and Development, 2025)
This study aims to analyze digital-based qurban services provided by the SEBISAKU (Semua Bisa Kurban) platform using the Analytical Network Process (ANP) method and the New Product Development (NPD) framework. This study involved 99 respondents who were a combination of active users, less active users and inactive users of the SEBISAKU platform. This study explores the parameters that affect SEBISAKU services based on respondents' perceptions and expectations using SERVQUAL, then elaborates these interrelated parameters using ANP to determine the priorities of all existing parameters. Furthermore, the priority parameters generated from ANP will be elaborated using Quality Function Deployment (QFD) to determine the functional and technical requirements needed for these interrelated parameters. Furthermore, this study analyzes all the results of the methods used in this study using NPD. The results of the study indicate that the services available on the SEBISAKU platform are currently still not in accordance with respondents' expectations (with a SERVQUAL value of -2.12). The combination of ANP, QFD and NPD used in this study shows that the SEBISAKU platform can be optimized by elaborating all parameters resulting from a series of methods used, customer-focused strategies, utilizing digital marketing techniques such as Guerilla Marketing that emphasizes low-cost marketing but can reach many people efficiently. The business model analysis shows that the operational approach of this platform is economically viable, with a positive Benefit-to-Cost (B/C) ratio in different logistics scenarios. The study also highlights that the introduction of new features and strategic marketing initiatives can significantly increase revenue, as well as improve user experience and business profitability, thus ensuring the success and sustainability of the platform in the long term.